PERUBAHAN SOSIAL PADA MASYARAKAT DALAM PERSPEKTIF AL-QUR`AN : (Studi Komparatif Tafsir At-Thabari) - Hasbi, Husnaini (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2023)
The Qur'anic verse that is often presented to show the view and message of the Qur'an about social change is surah al-Ra'd (13) If you look at the opinions of scholars in understanding the meaning contained in surah Q. S. al-Ra'd (13) about the social change, there will be quite diverse opinions. As an example of the diversity of understanding the meaning of social change contained in Q.S. al-Ra'd (13) can be seen in the translation of that verse which is included in the translation of the Ministry of Religion and the translation written by M. Quraish Shihab in his book of interpretation, Tafsir al-Mishbandh. Translation of Q.S. al-Ra'd (13) as stated in the Qur'an and its translation are as follows: